SIP‐Based Thermal Detection Platform for the Direct Detection of Bacteria Obtained from a Contaminated Surface. Issue 15 (15th January 2018) - van Grinsven, Bart; Eersels, Kasper; Erkens‐Hulshof, Sandra; Diliën, Hanne; Nurekeyeva, Kunya; Cornelis, Peter; Klein, Dionne; Crijns, Francy; Tuijthof, Gabrielle; Wagner, Patrick; Steen Redeker, Erik; Cleij, Thomas J.
Abstract : Surface detection of bacteria has been proven difficult and time‐consuming. Different recovery techniques yield varying numbers of bacteria. Subsequently, bacterial culturing, used for identification of these bacteria, will take several hours. In this article, the potential of a newly developed thermal biomimetic sensor for the detection of bacteria on surfaces is described. Previously this thermal biomimetic sensor has proven to be able to detect and quantify different bacteria in various liquid media such as buffer and spiked urine samples. In this article, laboratory surfaces are contaminated with increasing concentrations of Escherichia coli . Bacteria are recovered from the surfaces using commercially available swab rinse kits (SRK). A calibration curve is created by coating chips with surface‐imprinted polymers (SIPs), serving as synthetic bacteria receptors, and exposing them to increasing concentrations of E. coli . Next, concentrations of E. coli in the SRK buffer are measured and quantified. The results show that it is possible to detect E. coli recovered from surfaces. Although quantification has been proven difficult as the dynamic range of the sensor is relatively narrow and the bacterial load obtained by using SRK is low, the sensor is able to give an indication about the concentration present on the surface. The results in this article illustrate that the thermal biomimetic sensor is a fast, low‐cost, and label‐free device useful in surface detection of E. coli, and seems a promising tool for future on‐site bacterial detection. Abstract : The research presented in this paper demonstrates the application of a fast, low‐cost sensor for surface detection of bacteria. Bacteria are obtained from a contaminated surface using commercial swab rinse kits and the biomimetic sensor is able to detect the bacteria in a qualitative and quantitative manner within the hour. In this way, it offers a low‐cost, fast alternative for the current labor‐intensive and expensive gold standard detection techniques.